The influence of service quality on community satisfaction at the Tumori village office West Gunungsitoli subdistrict Gunungsitoli city: - Zebua, Ivan Doktrin Famohouni; Larosa, Yoel Melsaro; Hulu, Fatolosa; Waruwu, Sukaaro (ProBisnis : Jurnal Manajemen, 2024)
When it comes to meeting the requirements and desires of individuals and groups, service quality is everything that they hope for. Stated differently, service quality is primarily determined by two factors: the perceived and expected level of service. When the level of service provided satisfies expectations, it is considered to be of an ideal or good quality. On the other hand, a service's perceived quality is negatively impacted if it falls short of expectations. As a result, the ability of the service provider to continuously satisfy client expectations determines the quality of the service. People become unhappy when service delivery falls short of their expectations. If the services live up to expectations, people will be happier. The purpose of the study is to determine the degree to which community satisfaction at the Tumori Village Office, West Gunungsitoli District, Gunungsitoli City, is influenced by service quality, as well as the relationship between the two. Based on the research that has been conducted, it is concluded that service quality influences community satisfaction and shows that service quality has a positive influence on community satisfaction. The results of the research indicate that community satisfaction is positively impacted by service quality, and that service quality itself influences community contentment.